1988
DOI: 10.1007/bf00403006
|View full text |Cite
|
Sign up to set email alerts
|

Isolation of monoclonal antibodies reacting with peribacteriod membranes and other components of pea root nodules containing Rhizobium leguminosarum

Abstract: Plant and bacterial antigens contributing to nodule development and symbiosis in pea (Pisum sativum L.) roots were identified after isolation of a set of monoclonal antibody (McAb)-producing hybridoma lines. Rats were immunised with the peribacteriod material released by mild osmotic shock treatment from membrane-enclosed bacteroids of Rhizobium leguminosarum bv. viceae. In order to diversify the range of McAb specificities, this material was either used as immunogen directly (method 1), or after immunodepleti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
80
0
1

Year Published

1989
1989
2018
2018

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 121 publications
(82 citation statements)
references
References 33 publications
1
80
0
1
Order By: Relevance
“…This contrasts with single layered host-parasite interfaces of mycorrhizal cells from GIomus versiforme, where deposition of plant cell wall polysaccharides, such as un-esterified pectin and hydroxyproline-rich glycoproteins at the host-parasite interface, has also been detected (Bonfante-Fasolo et al 1992). Furthermore, Bradley et al (1988) observed labelling of peribacteroid membranes of Rhizobium leguminosarum and plant plasma membrane of Pisum sativum with arabinogalactan antibodies (MAC 209). Their labelling pattern is similar to the result we obtained with the AG/AGP-antibody (CCRC-M-8), the ema was labelled close to the ehm (Fig.…”
Section: Discussionmentioning
confidence: 99%
“…This contrasts with single layered host-parasite interfaces of mycorrhizal cells from GIomus versiforme, where deposition of plant cell wall polysaccharides, such as un-esterified pectin and hydroxyproline-rich glycoproteins at the host-parasite interface, has also been detected (Bonfante-Fasolo et al 1992). Furthermore, Bradley et al (1988) observed labelling of peribacteroid membranes of Rhizobium leguminosarum and plant plasma membrane of Pisum sativum with arabinogalactan antibodies (MAC 209). Their labelling pattern is similar to the result we obtained with the AG/AGP-antibody (CCRC-M-8), the ema was labelled close to the ehm (Fig.…”
Section: Discussionmentioning
confidence: 99%
“…Wild-type, cesa5-1, and sos5-2 seeds were labeled with JIM13 [epitope: Knox et al, 1991;Yates and Knox, 1994;Yates et al, 1996;Majewska-Sawka and Nothnagel, 2000], MAC207 [epitope: a-GlcA-(1,3)-a-GalA-(1,2)-a-Rha; Bradley et al, 1988;Pennell et al, 1989;Yates and Knox, 1994;Yates et al, 1996;Pattathil et al, 2010], JIM8 (epitope: arabinogalactan; Pennell et al, 1991;Majewska-Sawka and Nothnagel, 2000), and CCRC-M7 (epitope: recognizes 6-linked b-D-Gal oligomers that contain arabinose; Puhlmann et al, 1994;Steffan et al, 1995;Pattathil et al, 2010) antibodies (Supplemental Figs. S7 and S8).…”
Section: Sos5 and Cesa5 Act Independently To Promote Seed Mucilage Admentioning
confidence: 99%
“…The specificities of the primary antibodies JIM5 and JIM7 (CarboSource) have been extensively described (Liners et al, 1989;Knox et al, 1990;Knox, 1997;Willats et al, 2001aWillats et al, , 2001bWillats et al, , 2001cMacquet et al, 2007a;Pattathil et al, 2010;Xu et al, 2011). JIM13, MAC207, JIM8, and CCRC-M7 (CarboSource) have also been previously described (Bradley et al, 1988;Pennell et al, 1989Pennell et al, , 1991Knox et al, 1991;Puhlmann et al, 1994;Yates and Knox, 1994;Steffan et al, 1995;Yates et al, 1996;Majewska-Sawka and Nothnagel, 2000;Pattathil et al, 2010). CBM3a, specific to more crystalline cellulose, and CBM28, specific to more amorphous cellulose regions (Blake et al, 2006), were treated as primary antibodies in identical solutions before treatment with mouse anti-histidine (Qiagen).…”
Section: Microscopy and Image Analysismentioning
confidence: 99%
“…The anti-AGP mAbs were from immunizations with different kinds of plant cell preparations and extracts (Bradley et aL, 1988;Dewey et aL, 1997;Knox et al, 1989;Norman etaL, 1986;Pennell etal., 1989). Sugar beet (Beta vulgaris) cv.…”
Section: Plants and Molecular Probesmentioning
confidence: 99%